Development of smart visualisation platform for traffic management - Ding, Wei (Nanyang Technological University, 2023)
The necessity of autonomous environmental service vehicles in today's fast-paced, ever-evolving urban landscape cannot be overstated. With increasing urbanization and population growth, the demand for efficient and sustainable waste management and road cleanliness solutions is at an all-time high. Traditional manual methods are often labour-intensive, time-consuming, and prone to human error, making them less than ideal in addressing these challenges.